The Immediate Intramedullary Nailing Surgery Increased the Mitochondrial DNA Release That Aggravated Systemic Inflammatory Response and Lung Injury Induced by Elderly Hip Fracture - Li Gan; Jianfeng Zhong; Ruhui Zhang; Tiansheng Sun; Qi Li; Xiaobin Chen; Jianzheng Zhang (Hindawi Limited, 2015)
Conventional concept suggests that immediate surgery is the optimal choice for elderly hip fracture patients; however, few studies focus on the adverse effect of immediate surgery. This study aims to examine the adverse effect of immediate surgery, as well as to explore the meaning of mtDNA release after trauma. In the experiment, elderly rats, respectively, received hip fracture operations or hip fracture plus intramedullary nail surgery. After fracture operations, the serum mtDNA levels as well as the related indicators of systemic inflammatory response and lung injury significantly increased in the rats. After immediate surgery, the above variables were further increased. The serum mtDNA levels were significantly related with the serum cytokine (TNF-α and IL-10) levels and pulmonary histological score. In order to identify the meaning of mtDNA release following hip fracture, the elderly rats received injections with mtDNA. After treatment, the related indicators of systemic inflammatory response and lung injury significantly increased in the rats. These results demonstrated that the immediate surgery increased the mtDNA release that could aggravate systemic inflammatory response and lung injury induced by elderly hip fracture; serum mtDNA might serve as a potential biomarker of systemic inflammatory response and lung injury following elderly hip fracture.